Forage Production and Quality of BRS Capiaçu as a Response of Cutting Age and Nitrogen Application - J. P. Alves; S. S. Mendes; E. S. Galeano; M. A. P. Orrico Junior; T. Fernandes; M. Retore; A. C. A. Orrico; L. da S. Lopes (Tropical Animal Science Journal, 2022)
Capiaçu is a cultivar of elephant grass (Pennisetum purpureum Schum.), which is a promising species for use in ruminant feed and presents a high potential for biomass production. However, as this grass became subjected to different management strategies, fluctuations in biomass production were observed, reflecting on its nutritive value. The objective was to verify the effect of cutting age and nitrogen (N) application on the productivity and nutritional value of BRS Capiaçu. A randomized block design was used in a 3 × 3 factorial scheme: three cutting ages (60, 90, and 120 days) and three levels of nitrogen fertilization (0, 100, and 200 kg N/ha/year). The variables evaluated were: productivity and chemical composition of the leaf, stem, and whole plant fractions, besides the production of nutrients and efficiency of utilization of applied nitrogen (EUAN). There were interaction effects between cutting ages and N application on dry matter (DM), crude protein (CP), cellulose, hemicellulose, and lignin production. Plants cut every 120 days and fertilized with 100 or 200 kg N/ha had the highest annual DM production. Nitrogen fertilization was efficient in increasing the percentage of leaves and the production of CP and DM digestibility of the grass. The highest CP production (in kg/ha/year) was observed for the 60- and 90-days old grass fertilized with 200 kg of N/ha/year. Grasses that were cut every 90 days and that received nitrogen fertilization of 100 kg N/ha/year were the ones that presented the highest EUAN. The cutting at 90 days of age, associated with N fertilization of 100 kg N/ha/year, is the best strategy for BRS Capiaçu.